Numerical analyses of micro hygro-mechanical behaviours of wood fibre reinforced composites - Charupeng, N.; Kunthong, P. (Journal of Research and Applications in Mechanical Engineering, 2019)
In spite of their relatively low manufacturing costs and enhanced mechanical properties, wood fibre-reinforced composite materials have a number of drawbacks regarding the long-term durability. One of which, as commonly known, arises from the hygroexpansion subjected to moisture uptake. Various experimental studies have been performed to investigate the mechanical behaviours in multi-scale while considerably less attempts on micromechanical studies are published. This research is presented to simulate the hygroelastic behaviours of wood fibre-reinforced composites in microscopic scale. Hygroelastic strains in orthotropic directions are accounted for. Weak formulation Finite Element Method for hygroexpansion of wood fibre constituent is developed and the algorithm is implemented using MATLAB. Input data in the model are model dimensions, elastic constants, densities of both constituents, fibre weight fraction, hygroexpansion coefficients of wood fibre and relative humidity. The simulation results exhibits reasonable agreements with the experiments - sorption tests of birch fibres-PLA matrix composite from previous studies, especially at low wood contents. The models also confirms structural failure caused by hygroexpansion. This model aims to be a preliminary design tool for creating wood fibre-reinforced composites exposed to high relative humidity. Further studies can be done to investigate debonding and cracking behaviours under wet-dry cycles.